PENERAPAN METODE DEMONSTRASI UNTUK MEMPERBAIKI PROSES PEMBELAJARAN DAN MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS IV SD NEGERI 58 BALAI MAKAM KECAMATAN MANDAU - Mai Rianti (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2018)
This research is motivated by the problem of the low learning outcomes of students in natural science learning at elemantaryschool 58 Balai Makam, Mandau District. The purpose of this study was to improve the learning process and improve thelearning outcomes of science in the fourth grade students of elementary school 58 Balai Makam through the application ofdemonstration methods. The subjects of this study were fourth grade students totaling 26 people. This study consisted of twocycles. Student learning outcomes in cycle I obtained an average of 67.42 with 16 students who were completed and 10 studentswho were not completed, while in cycle II obtained an average of 75.80 with 22 students who were complete and 4 students whohad not complete. Based on the results of the research that has been carried out, it can be concluded that through thedemonstration method it has been proven to be able to improve the learning outcomes of students in grade IV elementary school58 Balai Makam.